Do children emotionally rehearse about their body image?. (September 2015) - Ling, Fiona CM; McManus, Alison M; Knowles, Gemma; Masters, Rich SW; Polman, Remco CJ
This study examined the association between propensity for emotional rehearsal, body image self-perception and weight status in Chinese Hong Kong pre-adolescents. Children 8–12 years of age ( n = 278) completed measurement of body mass index, body image and emotional rehearsal. Multinomial regression analyses revealed that body mass index was positively associated with body image dissatisfaction and a significant predictor of body size estimation. However, only body size underestimation was associated with lower rehearsal tendencies. The prevalence of body image dissatisfaction and body size estimation was also reported for this population. Future research is suggested for greater understanding of emotional coping in body image dissatisfaction in young children.